If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -3)(x + -5) = 64 Reorder the terms: (-3 + x)(x + -5) = 64 Reorder the terms: (-3 + x)(-5 + x) = 64 Multiply (-3 + x) * (-5 + x) (-3(-5 + x) + x(-5 + x)) = 64 ((-5 * -3 + x * -3) + x(-5 + x)) = 64 ((15 + -3x) + x(-5 + x)) = 64 (15 + -3x + (-5 * x + x * x)) = 64 (15 + -3x + (-5x + x2)) = 64 Combine like terms: -3x + -5x = -8x (15 + -8x + x2) = 64 Solving 15 + -8x + x2 = 64 Solving for variable 'x'. Reorder the terms: 15 + -64 + -8x + x2 = 64 + -64 Combine like terms: 15 + -64 = -49 -49 + -8x + x2 = 64 + -64 Combine like terms: 64 + -64 = 0 -49 + -8x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '49' to each side of the equation. -49 + -8x + 49 + x2 = 0 + 49 Reorder the terms: -49 + 49 + -8x + x2 = 0 + 49 Combine like terms: -49 + 49 = 0 0 + -8x + x2 = 0 + 49 -8x + x2 = 0 + 49 Combine like terms: 0 + 49 = 49 -8x + x2 = 49 The x term is -8x. Take half its coefficient (-4). Square it (16) and add it to both sides. Add '16' to each side of the equation. -8x + 16 + x2 = 49 + 16 Reorder the terms: 16 + -8x + x2 = 49 + 16 Combine like terms: 49 + 16 = 65 16 + -8x + x2 = 65 Factor a perfect square on the left side: (x + -4)(x + -4) = 65 Calculate the square root of the right side: 8.062257748 Break this problem into two subproblems by setting (x + -4) equal to 8.062257748 and -8.062257748.Subproblem 1
x + -4 = 8.062257748 Simplifying x + -4 = 8.062257748 Reorder the terms: -4 + x = 8.062257748 Solving -4 + x = 8.062257748 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + x = 8.062257748 + 4 Combine like terms: -4 + 4 = 0 0 + x = 8.062257748 + 4 x = 8.062257748 + 4 Combine like terms: 8.062257748 + 4 = 12.062257748 x = 12.062257748 Simplifying x = 12.062257748Subproblem 2
x + -4 = -8.062257748 Simplifying x + -4 = -8.062257748 Reorder the terms: -4 + x = -8.062257748 Solving -4 + x = -8.062257748 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + x = -8.062257748 + 4 Combine like terms: -4 + 4 = 0 0 + x = -8.062257748 + 4 x = -8.062257748 + 4 Combine like terms: -8.062257748 + 4 = -4.062257748 x = -4.062257748 Simplifying x = -4.062257748Solution
The solution to the problem is based on the solutions from the subproblems. x = {12.062257748, -4.062257748}
| (x-3)(x-5)=74 | | (x-3)(x-5)=84 | | (x+3)(x-5)=84 | | 3*x-x*log(x)=log(e^5) | | 3x-xln(x)=lne^5 | | 5x-7x-24=0 | | 4d^2-16-8d-d^2=0 | | x^3-24x^2+180x-424=0 | | 3x-xln(x)-9=(-4) | | 48=5x-28 | | 5+7x=9x-12 | | Log(x)12=5 | | y*(-3-y)=-10 | | -3y-y=-10 | | 15y-y=56 | | 3x^2-6x+1.625=0 | | f(1/2x)*(1/2x) | | 681=X+0.3X | | (0.45*1.6x)+(0.55*x)=6 | | (14/120)x(14/120)x(14/120) | | (0.45*1.6x)+(0.55*x)=3 | | 4x-9=ax-3a | | 4x-9=ax-3ax | | 4x-9=ax-3 | | 54-12x=16x+10 | | (0.6*2x)+(0.4*x)=6 | | X^2+y^2=6z | | 2=-x-1 | | 1=-x-1 | | z^3=-81 | | 3=4-2y | | 1=4-2y |